The effect of environmental conditions on the abundance of grubs of the cockchafer (Melolontha hippocastani F.) - M. Švestka; K. Drápela (Journal of Forest Science, 2009)
In selected sample plots which included pine forest plantations, pine young growth, small pole stage of pine, pine high forest, mixed pine/oak stand, beech stand and unforested land the bionomics and the abundance of grubs were studied between two swarmings of M. hippocastani F. cockchafers in the period from 2003 to 2007. On the basis of correlations between the abundance of grubs and course of daily temperatures during swarming, and characteristics of the sample plots, particularly the degree of shading, we evaluated the factors which affected the M. hippocastani F. females in their choice of the locality for laying eggs. The correlation between the abundance of grubs and the shading of the locality was evaluated statistically. On the basis of checks of the soil probes the development of grubs and changes in their numbers were monitored in the period from 2004 to 2006.